The Participatory Creative Music Hub: Process Over Product - Campbell, Louise; Hron, Terri (Performance Matters)

(untitled) (Institute for Performance Studies, Simon Fraser University, 2023)
A community-based project, the Participatory Creative Music Hub (the Hub) was developed by the Canadian New Music Network (CNMN) to research, create, and distribute an online resource to inspire creativity in music and sound for all. In addition to inspiring people of many backgrounds to create their own music, the process of building and sharing the Hub has helped to develop a sense of community among diverse creative practitioners across Canada. In doing so, it has raised questions about both the aesthetic and social values of music. In recent years, on an organizational level, CNMN’s focus and scope has transitioned from a primarily industry-focused network dedicated to building professional networks and opportunities to an outward-looking, knowledge- and resource-sharing network actively cultivating a more inclusive member base and connecting with other sectors. The Hub is one of the CNMN’s recent initiatives that is working to redefine the place of music in Canadian society and shift ideas around who can and does make New Music across Canada, and where, how and why people make music. In this article, we propose that the Hub also performs socially engaged practice-based research that models an expanded imaginary for creative music and sound in contemporary Canadian society.